2022
DOI: 10.35445/alishlah.v14i2.1298
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Academic Engagement, Lecturer’s Competence and Social Support to the Students’ Academic Achievement

Abstract: One of the goals of college is to educate students to have the ability to survive and advance in every development of the times. And among the skills that students must have is language mastery. Therefore, students need to have high academic engagement and support from the environment in which they study. This study aims to test the relationship of academic engagement to the achievement of Arabic learning achievement and test the effect of moderation of lecturer competence and social support on the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The manner by which student bills are paid is called expenditure; if a student's financial duties are not met, it has an effect on his or her success in school; on the other hand, if the students' financial needs are met, their performance in school may improve (Salameh et al, 2020). Academic achievement of children is supported by family income (Hanafi, 2008).…”
Section: Incomementioning
confidence: 99%
See 2 more Smart Citations
“…The manner by which student bills are paid is called expenditure; if a student's financial duties are not met, it has an effect on his or her success in school; on the other hand, if the students' financial needs are met, their performance in school may improve (Salameh et al, 2020). Academic achievement of children is supported by family income (Hanafi, 2008).…”
Section: Incomementioning
confidence: 99%
“…Marjoribanks (1998) found that parents had much greater levels of education than teenagers. (Portes, Zady, & Dunham, 1998) found that moms with lower levels of education had children who were less passionate about studying (Hanafi, 2008).…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation